The Influence of Leadership and Coordination on Employee Performance at Bali Bird Park, Gianyar Regency - Ni Kadek Ari Santi; Ni Made Tirtawati; Ida Bagus Gede Agung Widana (PT FORMOSA CENDEKIA GLOBAL, 2025)
Employee performance is a crucial factor in achieving a company's success because of its strong relationship to employee productivity. Work time discipline at Bali Bird Park is an indication of low employee performance. Coordination that is not yet optimal between leaders and employees, lack of direction and attention from leaders to the division of work and low cooperation between employees creates a bad image. This study aims to determine the effect of leadership and coordination on employee performance. Research data were obtained through a survey of all 86 employees. Data analysis was carried out using SPSS with Multiple Linear Regression Test, Classical Assumption Test and Determination Coefficient Test. It was found that the leadership variable positively and significantly influenced 6.0836% of employee performance. The coordination variable positively and significantly influenced 21.864% of employee performance. Simultaneously, the leadership and coordination variables positively and significantly influenced employee performance by 27.8%.